The Legal Construction of Land Boundary Designation: Efforts to Prevent Disputes in Land Administration - Muhamad Ansori; Iwan Permadi; Supriyadi (Правові горизонти, 2024)
Land boundary determination is a fundamental aspect of land administration in Indonesia, aimed at ensuring legal certainty and preventing disputes among landowners. Recent technological advancements, including the use of drones and photogrammetry as regulated in Permen ATR/BPN No. 3/Juknis-HK.02/III/2023, have significantly improved efficiency in land measurement processes. These technologies enable accurate data collection even in inaccessible locations and produce digital maps supporting the modernization of land administration. However, their application raises critical legal issues, particularly regarding violations of the rechtszekerheid principle (legal certainty) and contradictory delimitation, which require the direct presence of landowners and bordering parties. This study employs a normative legal method, focusing on statutory and conceptual approaches. The findings indicate that while drones and photogrammetry enhance efficiency, the absence of direct stakeholder involvement undermines the legitimacy of measurement outcomes. Regulatory revisions are necessary to integrate field validation, ensuring compliance with legal and technical standards. The conclusion emphasizes harmonizing technological advances with legal principles to create an efficient, transparent, and equitable land administration system that aligns with Indonesia's systematic land registration goals by 2025.